(untitled) (The Journal of Aadikavi, 2024)
This study discovers the techniques employed by English teachers in teaching writing skills at the secondary level in Tanahun District, Nepal, while identifying the key challenges they encounter. Adopting a mixed-method approach, the research incorporates questionnaires, classroom observations, and interviews with ten English teachers (five from public and five from private schools). Findings expose that teachers mostly use an eclectic approach, combining traditional grammar-translation methods with communicative language teaching (CLT) strategies, such as guided writing, free writing, and peer feedback. However, significant barriers hamper effective instruction, including large class sizes, insufficient teaching resources (e.g., audio-visual aids, textbooks), and students’ weak foundational skills in grammar and vocabulary. The study emphasizes the need for targeted teacher training programs, improved resource allocation, and policy reforms to develop writing pedagogy in secondary education. By highlighting these challenges and practices, the research offers valuable insights for curriculum designers, policymakers, and educators aiming to strengthen English language instruction in Nepal and similar contexts.